Analysis of Children's Drawings to Gain Insight into Plant Blindness. Issue 1 (1st September 2019) - Comeau, Paula; Hargiss, Christina L. M.; Norland, Jack E.; Wallace, Alison; Bormann, Anthony
Abstract : Core Ideas: Human figure drawing protocols were modified to assess children's plant drawings. When drawing plants in situ, students were unable to accurately represent plant characteristics. Drawings lacked detail and only contained prominent features, some contained inaccurate features. Students had over‐simplified mental models of plants, indicating plant blindness. It has been speculated that most people have plant blindness, meaning plants go unnoticed by the majority of the population. This study sought to combine the knowledge of multiple disciplines to determine evidence of plant blindness through children's drawings. To do this, third‐grade students were introduced to native prairie and wetland plants during a curriculum‐based field trip to a natural area to assess if youth accurately perceive plants in situ and had preconceived mental models of plant prototypes. Using a coding scheme from human figure drawing research, drawings were analyzed based on the plant characteristics represented in the drawings. Drawings showed the third graders oversimplified plants regardless of the macro‐features of the plant. Some drawings had inaccuracies, despite children being in close proximity to the designated plant. These results demonstrate plant mental models are already in place in this age group and may lead to plant blindness. Therefore, there is a need to start plant education as early as possible with more exposure to different plant types. This research represents one of the first studies to investigate the roots of "plant blindness" and what may be contributing to lack of knowledge and awareness of plant communities. It is the hope that the findings from this study will help professionals grow environmental literacy of plants across age groups.